The Influence of Profitability and Liquidity on Share Returns of Mining Sector Companies on the Indonesian Stock Exchange - Muhamad Halilullah; Susi Retna Cahyaningtyas (Formosa Journal of Multidisciplinary Research, 2024)
The researcher aims to see the effect of profitability and liquidity on the returns of coal mining shares included in the Indonesian Stock Exchange in 2018-2022. Profitability is measured by the Return On Assets ratio, while Liquidity is measured by the Current Ratio (CR). The type of research data is quantitative data using the coal mining population included in the Indonesian Stock Exchange (BEI). A sample of 15 companies with an observation period during the 2018-2022 period. Data analysis using the EVIEWS 12 application. The results show that Profitability and Liquidity have a positive effect on stock returns for coal mining sector companies included on the Indonesian Stock Exchange in 2018-2022.